Comparison of supine and prone miniaturized percutaneous nephrolithotomy in the treatment of lower pole, middle pole and renal pelvic stones: A matched pair analysis - Erbin, Akif (Int Braz J Urol, 2019)
PURPOSE: We aimed to compare the outcomes of supine and prone miniaturized percutaneous nephrolithotomy (m-PNL) in the treatment of lower pole, middle pole and renal pelvic stones. MATERIALS AND METHODS: 54 patients who performed supine m-PNL between January 2017 and March 2018 and 498 patients who performed prone m-PNL between April 2015 and January 2018 were included in the study. Of the 498 patients, 108 matching 1: 2 in terms of age, gender, body mass index, American Association of Anesthesiology score, stone size, stone localization and hydronephrosis according to the supine m-PNL group were selected as prone m-PNL group. The patients with solitary kidney, upper pole stone, urinary system anomaly or skeletal malformation and pediatric patients (<18 years old) were excluded from the study. The success was defined as ‘complete stone clearance’ and was determined according to the 1(st) month computed tomography. RESULTS: The operation time and fluoroscopy time in supine m-PNL was significantly shorter than prone m-PNL group (58.1±45.9 vs. 80.1±40.0 min and 3.0±1.7 min vs. 4.9±4.5 min, p=0.025 and p=0.01, respectively). When post-operative complications were compared according to the modified Clavien-Dindo classification, overall and subgroup complication rates were comparable between groups. There was no significant difference between the groups in terms of the success rates (supine m-PNL; 72.2%, prone m-PNL; 71.3%, p=0.902). CONCLUSIONS: Supine m-PNL procedure is more advantageous in terms of operation time and fluoroscopy time in the treatment of lower pole, middle pole and renal pelvic stones.